Spatiotemporal control of micromechanics and microstructure in acoustically-responsive scaffolds using acoustic droplet vaporization. Issue 28 (29th June 2020) - Aliabouzar, Mitra; Davidson, Christopher D.; Wang, William Y.; Kripfgans, Oliver D.; Franceschi, Renny T.; Putnam, Andrew J.; Fowlkes, J. Brian; Baker, Brendon M.; Fabiilli, Mario L.
Abstract : Acoustic droplet vaporization (ADV) of phase shift emulsion (green) generates different bubble morphologies, and spatiotemporally tunes the micromechanics of fibrin gels (red). Abstract : Acoustically-responsive scaffolds (ARSs), which are composite fibrin hydrogels, have been used to deliver regenerative molecules. ARSs respond to ultrasound in an on-demand, spatiotemporally-controlled manner via a mechanism termed acoustic droplet vaporization (ADV). Here, we study the ADV-induced, time-dependent micromechanical and microstructural changes to the fibrin matrix in ARSs using confocal fluorescence microscopy as well as atomic force microscopy. ARSs, containing phase-shift double emulsion (PSDE, mean diameter: 6.3 μm), were exposed to focused ultrasound to generate ADV – the phase transitioning of the PSDE into gas bubbles. As a result of ADV-induced mechanical strain, localized restructuring of fibrin occurred at the bubble–fibrin interface, leading to formation of locally denser regions. ADV-generated bubbles significantly reduced fibrin pore size and quantity within the ARS. Two types of ADV-generated bubble responses were observed in ARSs: super-shelled spherical bubbles, with a growth rate of 31 μm per day in diameter, as well as fluid-filled macropores, possibly as a result of acoustically-driven microjetting. Due to the strain stiffening behavior of fibrin, ADV induced a 4-fold increase in stiffness in regions of the ARS proximal to the ADV-generated bubble versus distal regions. These results highlight that the mechanical and structural microenvironment within an ARS can be spatiotemporally modulated using ultrasound, which could be used to control cellular processes and further the understanding of ADV-triggered drug delivery for regenerative applications.